Sacrifices and Rituals in Traditional African Medical Practices amongst the Yorubas, West Africa: Dynamics and Implications for Biodiversity Conservation - Soewu, Durojaye Adebola; Sodeinde, Olufemi A (American Journal of Human Ecology, 2017)
Appeasing gods, witches and ancestral spirits constitute an integral part of the traditional healing practices of Yorubas. Ten classes of sacrifice were identified, some with proven efficacy as specific requests presented were reported fully satisfied. Response from astral realm could signify acceptance, in which materials presented as sacrifice would be “consumed” within a stipulated time, or it could be ignored to indicate rejection. Most sacrifices have time and presentation-spot specificity. Preparation, presentation and post-presentation stages of most sacrifices were associated with various myths which include not looking back after presentation to avoid ‘spying’ on spirits. A wide variety of wild animals was utilised in preparing these sacrifices which are species-specific without any consideration for conservation interests. Preparations involved animals under varying degrees of threats as well as newborn, juvenile and pregnant animals. In addition to depleting the population, such requirements eat deep into the procreation base of the populations, denying several members the opportunity to participate in reproductive activities. There is an urgent need to improve yield of these animals, in-situ and ex-situ. There is also a need to reduce demand for, and utilisation of, these resources through massive conservation education, extension services and capacity building for indigenous people.